Making Meanings: Exploring Teachers’ Thinking in Adult Education - Janice Malcolm; Miriam Zukas (Adult Education Research Conference, 2002)
In this paper, we use two case studies of teachers to explore the relationship between disciplinary and pedagogic identities.